Compositional crossroads : music, McGill, Montréal - Stubley, Eleanor Victoria, 1960- (McGill-Queen's University Press, 2008)
McGill University's Faculty of Music - now the Schulich School - has been a centre of new music in Canada for decades, helping to shape contemporary composition, electro-acoustic research, performance, and sound recording. Compositional Crossroads focuses on McGill's location in a culturally dynamic city and shows how the interplay between place, community, identity, and memory and individuals, faculty, and students created institutional pathways that have lead to an explosion of new music activity.